Slope parameters determined from CREX and PREX2 - Shingo Tagami; Tomotsugu Wakasa; Masanobu Yahiro (Results in Physics, 2022)
Background:: Very lately, the CREX group presents a skin value ΔRskin48(CREX)=0.121±0.026(exp)±0.024(model)=0.071∼0.171 fm. Meanwhile, the PREX group reported a skin value ΔRskin208(PREX2)=0.283±0.071=0.212∼0.354 fm. In our previous paper, we determined both the L–ΔRskin48 relation and the L–ΔRskin208 one, using 206 EoSs, where L is a slope parameter. Purpose:: We determine L from ΔRskin48(CREX) and ΔRskin208(PREX2), using 207 EoSs. Results:: The ΔRskin48(CREX) yields L(CREX)=0∼51MeV and the ΔRskin208(PREX2) does L(PREX2)=76∼165MeV. Conclusion:: There is no overlap between L(CREX) and L(PREX2). This is a big problem to be solved.